2020
DOI: 10.1111/evj.13392
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokines in horses with cervical articular process joint osteoarthritis on standing cone beam computed tomography

Abstract: Background Standing cone beam computed tomography (CT) provides cross‐sectional imaging of the caudal cervical articular process joints (CAPJs) in the sedated horse, though the clinical implications of osteoarthritis (OA) identified on CT in this location are unknown. Increases in concentrations of intra‐synovial cytokines could lend support to the clinical significance of CAPJ OA identified on this imaging modality. Objectives Investigate the presence and concentration of intra‐synovial inflammatory cytokines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…In general, OA is classified as non-inflammatory arthritis and is predominantly a degenerative disease of old age [ 27 ]. However, with further study of OA, immunity is considered to be an important part of OA pathogenesis [ 41 , 42 ]. Except for multiple signaling pathways, our results found that hypoxia was correlated with multiple immune cells in OA.…”
Section: Discussionmentioning
confidence: 99%
“…In general, OA is classified as non-inflammatory arthritis and is predominantly a degenerative disease of old age [ 27 ]. However, with further study of OA, immunity is considered to be an important part of OA pathogenesis [ 41 , 42 ]. Except for multiple signaling pathways, our results found that hypoxia was correlated with multiple immune cells in OA.…”
Section: Discussionmentioning
confidence: 99%
“…The release of inflammatory cytokines is one of the important inducing factors of OA (19). IL-1β serves an important role in altering the normal structure and function of chondrocytes, promoting the apoptosis of chondrocytes, degrading chondrocyte ECM, participating in synovial inflammatory lesions and affecting bone metabolism (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…The advent of large-bore and robotic scanner designs has allowed routine accommodation of the entire cervical spine and the cranialmost thoracic vertebrae in live adult horses (Figure 4). [125][126][127][128][129] This has enhanced our diagnostic abilities significantly, as radiography of this area is limited by superimposition, the degree of muscle mass present, and the reality of only being able to obtain lateral-lateral and oblique views in the adult horse. Ultrasonography can only evaluate the bony margins of the vertebral canal and not the soft tissues within it.…”
Section: Cervical Spinementioning
confidence: 99%